Hepatic resection for bile duct injury: A case report - Joshi, Utsav; Bhandari, Ramesh Singh (Journal of Chitwan Medical College, 2017)
Background: Bile duct injury is a serious complication following both open and laparoscopic cholecystectomy. The extent of injury may be severe enough to consider biliary reconstruction procedures like Roux-en-Y hepaticojejunostomy or even hepatectomy in rare instances for the definitive management. Case: A 56 year old female, who underwent open cholecystectomy and detected bile duct injury intraoperatively. Small feeding tube was placed in the bile duct, exteriorized and patient was referred to our center for further management. Liver function tests at presentation revealed cholestatic patterns of liver derangement but the patient did not show any signs suggestive of sepsis. Endoscopic Retrograde Cholangiopancreatography revealed complete stricture of common hepatic duct. Magnetic Resonance Cholangiopancreatography revealed Bismuth type 4 bile duct stricture. The plan was to perform a bilateral hepaticojejunostomy, however, because of the very difficult anatomy and failure to identify the right duct, right hepatectomy with left duct hepaticojejunostomy was performed as a definitive management for her type IV bile duct injury. The patient had an uneventful post-operative course. Conclusion: Infrequently, liver resection remains an important therapeutic option in cases of complicated and major forms of bile duct injuries where the bilateral biliary reconstruction is not feasible.